CLINICAL AND LABORATORY FEATURES OF RESPIRATORY SYNCYTIAL VIRAL INFECTION IN YOUNG CHILDREN - Yusupova, Gulnoza; Israilova, Nigora (Medical science of Uzbekistan, 2025)
Relevance. Respiratory syncytial infection is the most common cause of lower respiratory tract damage in children under 5 years of age. Respiratory syncytial virus infection is the most common cause of severe lower respiratory tract disease in children, with the development of bronchiolitis, obstructive bronchitis and pneumonia.The purpose was to study the clinical and laboratory characteristics of respiratory syncytial virus infection in young children. Materials and methods of the study. A general clinical examination, PCR of nasopharyngeal swabs for respiratory viruses, and bacteriological examination of throat and nasal swabs for pathogenic flora were carried out. 45 young children hospitalized in a hospital with laboratory confirmed MS infection. Research results. It was established that the disease occurs with a slightly pronounced intoxication-febrile syndrome against the background of moderate catarrhal symptoms. The severity is determined by respiratory failure due to the development of obstructive bronchitis, which is registered in 84.2% of cases, bronchiolitis, which is diagnosed in every third young patient, and, less commonly, pneumonia (15.8%). Conclusion. Children under one year of age are characterized by a severe course due to obstructive bronchitis, bronchiolitis or pneumonia with the development of severe respiratory failure.